2019
DOI: 10.1063/1.5128771
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal physical behaviors of hafnium diboride under high pressure

Abstract: Hafnium diboride (HfB2) is one of the most promising hard-brittle ceramic materials with unique physical properties. Here, we have synthesized the well-crystallized HfB2 by a high-pressure solid-state reaction and employ in situ high-pressure synchrotron radiation angle-dispersive X-ray diffraction to investigate the size-effect of HfB2. An abnormal physical behavior of HfB2 under high pressure is observed. The microsized HfB2 shows slight anisotropy along a and c axes; however, the nanosized HfB2 reveals a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In addition, the strength–pressure data also show that the HfC crystallite undergoes plastic deformation at about ∼25 GPa, where microstress (a measure of the compressive strength) describes its yield strength, resulting in a yield strength of ∼18 GPa. As shown in Figure b, the yield strength of HfC is lower than those of HfB 2 (∼19 GPa) and B 6 O (∼30 GPa) and slightly higher than that of Al 2 O 3 (∼17 GPa) . Previous studies reported that the Vickers hardness values of HfB 2 , B 6 O, and Al 2 O 3 are 26, 45, and 20 GPa, respectively. According to the potential relationship between the strength and hardness, the Vickers hardness of HfC is inferred to be about 20–30 GPa, which is a relatively high hardness material.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the strength–pressure data also show that the HfC crystallite undergoes plastic deformation at about ∼25 GPa, where microstress (a measure of the compressive strength) describes its yield strength, resulting in a yield strength of ∼18 GPa. As shown in Figure b, the yield strength of HfC is lower than those of HfB 2 (∼19 GPa) and B 6 O (∼30 GPa) and slightly higher than that of Al 2 O 3 (∼17 GPa) . Previous studies reported that the Vickers hardness values of HfB 2 , B 6 O, and Al 2 O 3 are 26, 45, and 20 GPa, respectively. According to the potential relationship between the strength and hardness, the Vickers hardness of HfC is inferred to be about 20–30 GPa, which is a relatively high hardness material.…”
Section: Resultsmentioning
confidence: 90%
“…The grain size and strain at each pressure are determined by the intercept and slope of the straight line drawn from the data points. Estimation of the grain size usually has a rather large error, which is inherent in such experiments and is mainly caused by the use of short-wavelength radiation in the diffraction experiment with the DAC. , Figure a shows the grain size at different pressures. It is clear from Figure a that with the pressure increases from atmospheric to ∼25 GPa and the grain size steeply decreases from 320 (20) to 24 (8) nm and remains almost constant at higher pressure (above 25 GPa).…”
Section: Resultsmentioning
confidence: 99%
“…The temperature and pressure were accurate to ±10 °C and ±0.1 GPa, respectively. More detailed experimental procedures can also be found elsewhere. In the consolidation experiment, the samples were regularly compressed to 15 GPa at room temperature. After the pressure became stable, the samples were gradually heated to the desired consolidation temperature of 1100–1900 °C at a rate of 100 °C/min and held for 10 min to ensure that the temperature was uniform.…”
Section: Experimental Proceduresmentioning
confidence: 99%
“…But the full understanding of how temperature or/and pressure (extreme conditions) affect the HETMC performance have not been explored experimentally before. High pressures as one of the basic parameters besides temperature can change the interatomic distance or even bonding patterns and electronic configuration to control the material structure and performance. Lately, it was found that HEAs and high-entropy oxides (HEOs) with seemingly ultrastable structures demonstrate rich polymorphism at room temperature and high pressure. So, what are the structures and properties in HETMCs under high pressure?…”
Section: Introductionmentioning
confidence: 99%